Firearm-related deaths and crime in the autonomous city of Buenos Aires, 2002 - Spinelli, Hugo (2006)
Violence is one of the most serious challenges in Latin American societies. Possession and use of small arms and light weapons are considered to be among the main factors behind it. The aim of this paper is to describe deaths and crimes involving the use of a firearm in the City of Buenos Aires in 2002, focusing the health, justice and police sectors. Data on mortality and crimes were obtained from the National Systems for vital statistics and criminal information; data on firearm seizures were supplied by the Argentine Federal Police. Household interviews conducted for a previous research on firearm-related victimization were also used. An index of violent incidents was developed by police station. There were 1,304 deaths from violence, of which 23.7% were caused by a firearm. The police filed 171 proceedings on the charge of homicides with criminal intent, of which 60% had been committed with a firearm. Of the 2,108 interviewed individuals, 6.7% were victims of a crime committed with a firearm. In 9.6% of surveyed households there was a firearm. Seized firearms added up to 1,887. The index of violent incidents was higher in police stations in the southwestern area of the city that has worse living conditions. The impact of violence and its relation to firearms features as a major issue in the public agenda.